Reflexões sobre um curso de extensão universitária a partir da avaliação dos professores cursistas - Faria, Rejane Waiandt Schuwartz de Carvalho [UNESP]; Chinellato, Tiago Giorgetti [UNESP]; Maltempi, Marcus Vinicius [UNESP]; Javaroni, Sueli Liberatti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents the context of realization of university extension course "Proportional Reasoning: activities with GeoGebra integrating arithmetic, geometry and algebra" done with mathematics teachers of Basic Education of the public schools of the state of São Paulo. The course was marked by a mutual learning environment that presented activities relating Proportional Reasoning in their arithmetic, geometric and algebraic aspects in GeoGebra software. The various possibilities of analysis of the data that emerged in the course, this article will focus on the assessment made by the participating teachers regarding the format and the methodology adopted. Thus, our goal is to present a reflection on the course in order to share the good points of the format adopted in our approach and present the points that should be rethought and improved in this type of course.

Este trabalho apresenta o contexto da realização do curso de extensão universitária “Raciocínio Proporcional: atividades com o GeoGebra integrando aritmética, geometria e álgebra” realizado com professores de Matemática da Educação Básica da rede pública do estado de São Paulo. O curso foi marcado por um ambiente de mútua aprendizagem que apresentava atividades relacionando o Raciocínio Proporcional em suas vertentes aritmética, geométrica e algébrica no software GeoGebra. Das diversas possibilidades de análise dos dados que emergiram no curso, neste artigo iremos focar na avaliação feita pelos professores participantes no que tange o formato e a metodologia adotados. Deste modo, nosso objetivo é apresentar uma reflexão acerca do curso, a fim de compartilhar os pontos positivos do formato adotado na nossa abordagem, bem como apresentar os pontos que devem ser repensados e aprimorados neste tipo de curso.
Keywords: Mathematics education; Continued training; Digital technologies; Educação matemática; Formação continuada; Tecnologias digitais